Images of psychiatry and psychiatrists - Stuart, H (Acta Psychiatr Scand, 2015)
OBJECTIVE: This study surveyed medical teaching faculty to determine their attitudes toward psychiatry and psychiatrists. METHOD: We conducted a multisite survey of a probability sample of 1057 teaching medical faculty members from 15 academic teaching centers in the United Kingdom, Europe, and Asia stratified by early, middle, and late career stage. The average response rate across countries was 65%. RESULTS: The outstanding findings were that 90% of respondents considered that psychiatrists were not good role models for medical students, 84% thought psychiatric patients were unsuitable to be treated outside of specialized facilities, and 73% thought psychiatric patients were emotionally draining. We noted statistically significant differences by country, gender, career stage, and specialty. CONCLUSION: These results highlight why recruitment into psychiatry is problematic in many countries and suggest that greater attention should be given to improving the perception of psychiatrists as good role models and the efficacy of psychiatric treatments.